Red Kant : aesthetics, Marxism, and the third critique - Wayne, Mike (Bloomsbury studies in philosophy., 2014)
Is Kant really the 'bourgeois' philosopher that his advocates and opponents take him to be? In this bold and original re-thinking of Kant, Michael Wayne argues that with his aesthetic turn in the Third Critique , Kant broke significantly from the problematic philosophical structure of the Critique of Pure Reason . Through his philosophy of the aesthetic Kant begins to circumnavigate the dualities in his thought. In so doing he shows us today how the aesthetic is a powerful means for imagining our way past the apparent universality of contemporary capitalism. Here is an un.